Malignancy-associated hemophagocytic lymphohistiocytosis in pediatric cases: a multicenter study from Turkey - (:unkn) unknown (TURKISH J PEDIATRICS, 2009)
This study evaluates the clinical and laboratory data of children with secondary hemophagocytic lymphohistiocytosis (sHLH) related to malignancy. Charts of patients who met the diagnostic criteria for sHLH associated with malignancy between January 2000-2006 at six different hospitals in Turkey were reviewed retrospectively. The diagnosis of HLH had been established by bone marrow aspiration in 27 patients, cerebrospinal fluid and bone marrow aspiration in one patient and lung-liver biopsy in another. Twenty-nine children were diagnosed as having sHLH related to malignancy. Twenty cases (18 ALL and 2 AML) with acute leukemia (10 girls/10 boys, median age: 8 years [3-14 years]) were found to have sHLH. Five patients with acute leukemia had HLH at the time of diagnosis (Group 1a), and 15 patients with acute leukemia were diagnosed as having sHLH during therapy (Group 1b), namely reactive sHLH associated with the chemotherapy. Nine patients, including two cases each of rhabdomyosarcoma, neuroblastoma, Hodgkin disease, and non-Hodgkin lymphoma (NHL) and one case with Langerhans cell histiocytosis, were diagnosed as having concomitant hemophagocytosis at the initial evaluation of the tumor (Group 2). Fever, anemia, and hypertriglyceridemia were present in all sHLH cases of all three groups. Hepatomegaly was detected in 60.0%, 73.3%, and 88.8% of the three groups, respectively. Splenomegaly was more frequent in patients of Groups la (60.0%) and 2 (88.8%) than in those of Group 1b, the reactive ones (13.3%). Hypofibrinogenemia was detected in all patients of Group la and Group 2. Low level of fibrinogen was present in 91.6%% of patients in Group 1b. All patients in Group 1b (100%) had neutropenia and thrombocytopenia. Neutropenia was found at rates of 60.0% and 55.5% in Group la and Group 2, respectively. Thrombocytopenia was detected in 80.0% of patients in Group la and 77.7% in Group 2. The overall mortality rate was 34.4% (10 cases) in our series of 29 children with sHLH; 50% of deaths were directly attributable to HLH. Pediatric malignancy-associated HLH patients have been commonly described as case presentations or in a review of the literature. We believe that our cohort, compiling 29 children regarding the association between malignancy and HLH, will be useful for pediatricians who are interested in this still mysterious topic.
Keywords: hemophagocytic lymphohistiocytosis; malignancy; chemotherapy-related; acute leukemia; solid tumors; AMINO-ACID CHANGE; ADULT PATIENTS; PERFORIN; MUTATIONS; LYMPHOMA; A91V; FORM